The Impact of Socio-Environmental Parameters on the Development of Children and Adolescents in Altai Republic - VORONKOV, Evgeniy G.; VORONKOVA, Elena G. (Journal of Environmental Management and Tourism, 2019)
The problem of creating an environmentally friendly biosphere-compatible environment is one of the most acute. Therefore, the paper analyzes the impact of socio-hygienic parameters on the environment. To achieve this goal, the authors carried out a survey, which allowed to determine the impact of the quality of life on the younger generation and, accordingly, on the environment. It is known that the comfort of the climate, height above sea level, eastern longitude and latitude also affect the environmental component. It has been established that nutrition, as a hygienic indicator, is directly related to environmental pollution. Since the food industry is one of the main industries in the Altai Territory. The food industry is directly related to environmental issues as follows. It has been established that among the various factors of socio-economic nature that affect the growth and development of children, the level of average per capita income per family member is of great importance. Which are indicators of the quality of life of the population. And the influence of this population on the components of the environment.